SUSTAINABLE HOME GARDENS FOR FOOD SECURITY: AN EVALUATION OF THE PEKARANGAN PANGAN LESTARI (P2L) PROGRAM IMPLEMENTATION IN KOLAKA DISTRICT, INDONESIA - KHAERAH, MIFTAHUL; NARA, NURDIN (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Global food insecurity remains a critical challenge for developing nations, particularly rural communities facing vulnerabilities from climate variability, supply chain disruptions, and market dependency. This study presents a comprehensive mixed-methods evaluation of the Sustainable Home Garden Program (P2L), a household-level food security intervention, employing Dunn's policy evaluation framework across six critical dimensions: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. Data were collected between January and June 2024 across 12 sub-districts from 20 purposively selected informants including women's farmer group leaders, agricultural extension officers, and government officials. Methods included in-depth semi-structured interviews (60-90 minutes each), participatory observation of 13 program activities, and secondary document analysis. High-performing women's farmer groups demonstrated 85% reduction in market dependency, enhanced dietary diversity from 3-4 to 8-10 vegetable varieties, and achieved cost efficiencies of 40-60% through organic practices and innovative input management. Conversely, underperforming groups exhibited only 35% seedling cultivation success rates and minimal household food security improvements. Critical factors determining success included quality leadership, social cohesion, responsive governance mechanisms, and consistent technical support. Significant challenges identified encompassed seasonal water scarcity affecting 60% of gardens, uneven extension service coverage, absence of sustainability mechanisms post-program conclusion, and insufficient alignment with local agro ecological conditions and cultural preferences. Findings underscore that external input provision alone proves insufficient; sustainable food security improvements require integrated organizational capacity development, adaptive management systems, digital communication infrastructure, decentralized procurement approaches, and participatory variety selection processes. These evidence-based recommendations contribute to advancing context-specific food security interventions applicable to diverse socio-ecological settings where geographic heterogeneity and institutional fragmentation necessitate nuanced, place-based programming approaches.